1981
DOI: 10.1149/1.2127625
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitive Novolac‐Based Positive Electron Resist

Abstract: A positive electron resist has been developed which appears to operate on a different mechanism from conventional positive electron resists. Resists in the latter category such as PBS or PMMA achieve differential solubility primarily as a result of scission of the main chain. In the case of the new resist, differential solubility appears to be achieved by the removal of a polymeric dissolution inhibitor. The resist is a composite system consisting of a novolac resin similar to that used in most positive photor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…The effect of the developer and the development conditions on these parameter values are discussed. A similar effect of the used developer on the contrast value yd for electron lithography of Amil Acetate layers is shown in [4] and in the case of PMPS & Novolak in [ 5 ] . In addition in the ref.…”
Section: Introductionsupporting
confidence: 61%
“…The effect of the developer and the development conditions on these parameter values are discussed. A similar effect of the used developer on the contrast value yd for electron lithography of Amil Acetate layers is shown in [4] and in the case of PMPS & Novolak in [ 5 ] . In addition in the ref.…”
Section: Introductionsupporting
confidence: 61%
“…In their resist, slower dissolution rates and a longer induction period are clearly linked to the presence of oxygen during the PAB. 10 Empirical evidence for the oxidation theory is that the bake temperature has a large effect on the shape and extent of surface inhibition, a result reported by many researchers. 10,17,27 In this work, the oxidation theory was examined by confirming the effect of bake temperature on dissolution rate and estimating the sorption/concentration gradient of oxygen at various bake temperatures.…”
Section: Introductionmentioning
confidence: 90%
“…This is by far the weakest theory for surface inhibition, since surface inhibition is known to occur in pure novolac resin with no added PAC. 10 Also, if PAC segregated to the surface causing surface inhibition in unexposed areas, heavily exposed areas would inevitably show surface enhancement. To the knowledge of the authors, that effect has never been observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…His group developed a positive electron beam resist NPR [2]. NPR represented an entirely new approach to electron resist design.…”
mentioning
confidence: 99%